Dielectric studies of polycrystalline bismuth titanate Bi12TiO20 ceramic synthesized via economical chemical route - Verma M.K.; Singh L.; Kumar A.; Kumar V.; Singh N.B.; Mandal K.D. (My University, 2025)
Bismuth titanate nanostructure, Bi12TiO20, (BTO) belonging to sillenite family was synthesized by chemical route at the sintering temperature 800 °C for a period of 6 h. The crystalline phase of the materials was investigated by the X-ray diffraction method. The morphology and particle size of the BTO sample were determined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis, respectively. The SEM images displayed the bimodal structure, and average grain size was found to be in the range of 0.6–3.7 µm. TEM observation confirmed the nanocrystalline nature of the particle having size of 50 ± 20 nm. The value of dielectric constant and dielectric loss for Bi12TiO20 ceramic was found to be 8.29 × 103 and 3.27, respectively, at the temperature 468 K and frequency 100 Hz. © 2020, Indian Association for the Cultivation of Science.